2016
DOI: 10.1152/ajpheart.00894.2015
|View full text |Cite
|
Sign up to set email alerts
|

Muscle metaboreflex and cerebral blood flow regulation in humans: implications for exercise with blood flow restriction

Abstract: We investigated the effect of activating metabolically sensitive skeletal muscle afferents (muscle metaboreflex) on cerebral blood flow and the potentially confounding influence of concomitant changes in the partial pressure of arterial carbon dioxide. Eleven healthy males (25 ± 4 yr) performed submaximal leg cycling exercise on a semirecumbent cycle ergometer (heart rate: ∼120 beats/min), and assessments were made of the partial pressure of end-tidal carbon dioxide (PetCO2 ), internal carotid artery blood flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 62 publications
1
14
0
Order By: Relevance
“…; Edgell and Stickland ; Prodel et al. ). ETCO 2 is also reduced in women during PECO despite the absence of hyperventilation; however, tidal volume does increase slightly but significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Edgell and Stickland ; Prodel et al. ). ETCO 2 is also reduced in women during PECO despite the absence of hyperventilation; however, tidal volume does increase slightly but significantly.…”
Section: Discussionmentioning
confidence: 99%
“…; Prodel et al. ). However, when hypocapnia was prevented by eucapnic clamping, and mean arterial pressure (and presumably sympathetic activity) remained elevated, there was no reduction in MCA conductance implying that cerebrovascular constriction during PECO was due to changes in CO 2 only (Braz et al.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that increased anaerobic energy production may evoke higher metaboreflex activity and, consequently enhance heart rate (HR) response, cardiac output, and ventilation ( ) to adequately supply O 2 to exercising muscle and remove the metabolites generated from the anaerobic metabolism [ 11 13 ]. As a result, this compensatory mechanism produced by local hypoxia, together with a reduced venous return characteristic of BFR training, may overload central components of the cardiorespiratory system and lead to improvement in [ 14 , 15 ]. Furthermore, Egan et al [ 8 ] showed that higher blood lactate ([La - ] net ) accumulation, indicating greater contribution of the anaerobic metabolism, can result in significantly higher metabolic stress and consequently enhance mitochondrial biogenesis synthesis, a local factor which can also induce greater .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, despite much work in recent years, the regulation of CBF is still incompletely understood (8,36). It can be assessed by laser Doppler flowmetry, which, based on the noninvasive quantification of blood flow velocity (16), allows to differentiate areal-dependent changes of microperfusion in the cortex and subcortex.…”
mentioning
confidence: 99%